Challenges in 3D CFD Modelling of Rotary Positive Displacement Machines. Issue 1 (May 2021) - Kovacevic, Ahmed; Rane, Sham
Abstract: The use of Computational Fluid Dynamics (CFD) and Computational Continuum Mechanics (CCM) for analysis of rotary positive displacement machines is exponentially increasing which was mostly allowed by the development of methods for generating numerical grids of complex domains within the machines. However there are several challenges with the commercial CFD/CCM codes which are preventing generic use of CFD. These are conservativeness of spatial discretisation caused by the inappropriate grid generation, numerical instabilities and dissipations caused by misalignments and application of inappropriate discretisation of equations and the speed and accuracy of multiphase models used in CFD of positive displacement machines. In this paper the authors will review methods used for modelling of rotary positive displacement machines and challenges which developers and users of these methods face. The paper will also offer some solutions and directions for resolving these issues.